Sioranove vježbe nepokornosti - S. Kalezić-Radonjić, Svetlana (Slavia Centralis, 2020)
The fundamental objective of this paper is to determine the system of Cioran’s philosophical non-system. The entire opus of this philosopher offers an abundance of lucid and extraordinary analyses of the phenomenon of God, art (mostly music and poetry), and the meaning of life. At the center of his obsessions is the standpoint about the impotence of mankind, destined to endless recurrences of trouble and misery, to fundamentally change its position, which, in his opinion, was largely contributed by religion and God, which man created to explain his pain, misery and inner temptations. Although seemingly chaotic and contradictory, Cioran’s philosophical thought is primarily anti-dogmatic, as well as its literary expression, and it is characterized by great poetic “density.” Deriving from the profound personal feeling of tragedy of existence, it is oriented at life itself, and, as such, refuses to be systematized.